Mortality and heart failure in patients with severe tricuspid regurgitation. Impact of RV volumes and function by CMR. (14th October 2021) - Hinojar Baydes, R; Garcia-Martin, A; Gonzalez-Gomez, A; Monteagudo, J M; Pascual-Izco, M; Alonso-Salinas, G; Rivas Garcia, S; Fernandez-Mendez, M A; Garcia De Vicente, A; Zamorano, J L; Fernandez-Golfin, C
Abstract: Background and objectives: Right ventricle (RV) dilatation and dysfunction are established criteria for intervention in patients with significant tricuspid regurgitation (TR); however defined thresholds to support intervention are lacking. As a result the optimal timing for surgery in TR remains controversial and surgery is commonly undertaken at a late stage. Purpose: To describe predictive cut-off values of RV size and function of poor prognosis in asymptomatic patients with significant TR. Methods: Consecutive patients in stable clinical condition evaluated in the Heart Valve Clinic with significant TR (severe, massive or torrential TR) undergoing a Cardiac Magnetic Resonance (CMR) study were included. Conventional parameters of biventricular volume and function were assessed in all patients. A combined endpoint of hospital admission due to right heart failure and cardiovascular mortality was defined. Results: 75 patients were included in this study (age 75±8 years, 75% female, 91% functional TR). During a median follow-up of 3 years (IQR: 1.4–3.9 years), 39% of the patients (n=29) experienced the combined endpoint. After adjusting for age and LVEF in a multivariate Cox proportional model, RV-EDV and RVEF were independently associated with cardiovascular mortality and heart failure. Thresholds of RV-EDV ≥100 ml/m 2, RV-ESV ≥40 ml/m 2 and RVEF ≤58% held the best accuracy to predict outcomes (figure 1). Regression spline model for RVEF and outcomes are presented in the figure 2. They show that RV function negatively impacted event-free survival, with an increase in the HR spline function near the crossing value (red line, RVEF ≤58%). In multivariable analysis, following adjustment for age and LVEF, a value of RVEF ≤58% and RV-EDV ≥100 ml/m 2, was associated with 2.29, and 3.91-fold increased risk of heart failure or cardiovascular death respectively (RVEF Hazard Ratio (HR): 2.29 [1.06–4.9], p=0.03, and RV-EDV HR: 3.91 [1.56–9.82], p=0.004). Conclusion: RV size and function are crucial for determining optimal timing for TR intervention. For the first time, cut-off values of RV volume and function are defined in a cohort of consecutive patients based on outcome data. Proposed values provide a basis for prospective studies to establish definitive optimal surgical timing for severe TR. Funding Acknowledgement: Type of funding sources: None.